2018
DOI: 10.1007/s00170-017-1474-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and trend of condition monitoring and fault diagnosis of multi-sensors information fusion for rolling bearings: a review

Abstract: A rolling bearing is an essential component of a rotating mechanical transmission system. Its performance and quality directly affects the life and reliability of machinery. Bearings' performance and reliability need high requirements because of a more complex and poor working conditions of bearings. A bearing with high reliability reduces equipment operation accidents, equipment maintenance costs and achieves condition-based maintenance. First in this paper, the development of technology of the main individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(86 citation statements)
references
References 131 publications
0
82
0
Order By: Relevance
“…Recently, non-invasive methods have been developed, e.g., acoustic, vibrational, thermal, magnetic methods [11][12][13]. Non-invasive methods are capable of diagnosing early faults without disassembly of the induction motor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, non-invasive methods have been developed, e.g., acoustic, vibrational, thermal, magnetic methods [11][12][13]. Non-invasive methods are capable of diagnosing early faults without disassembly of the induction motor.…”
Section: Introductionmentioning
confidence: 99%
“…Condition monitoring of electric motors was developed for measurement and analysis of diagnostic signals such as acoustic [1,2], thermal [3,4], electric current [5][6][7], and vibration [8][9][10][11][12][13]. Each type of signal has advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that the approach was effective for detection of different faults of rolling bearings [9]. Duan et al [10] described the development of condition monitoring of rolling bearings using vibration analysis, acoustic analysis, oil analysis, temperature analysis, and ultrasonic analysis. e authors indicated that multisensors information fusion is the trend of development [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bearing failure is a dynamic process, it is insufficient to know whether there is any fault or the fault type for the preventive maintenance of bearings in engineering applications. Determining the failure evolution process and accurately monitoring the fault severity are paramount for an effective bearing maintenance [4][5][6]. Consequently, the fault severity monitoring of rolling bearings is becoming increasingly important [7,8].…”
Section: Introductionmentioning
confidence: 99%